\(\mathcal{O}(α^3)\) ISR Corrections to Single Higgs Productions at Future Lepton Colliders - Khiem, Phan Hong; Dzung, Tran Tri (Communications in Physics, 2019)
In this paper, we present \(\mathcal{O}(α^3)\) QED corrections due to initial-state photon radiation (ISR) to processes \(e^{−} e^{+} → f \bar{f} H\) with \(f = e, μ_e, u_{μ}, u_{τ}\) at future lepton colliders. The impact of the ISR corrections on the total cross sections are studied. We find that the corrections vary from ∼ −30% to −10% in the range of center-of-mass energies from 200 GeV to 700 GeV. The ISR corrections to some realistic distributions of experimental interest for searching the properties of the Higgs boson are also evaluated and they are order of \(\sim −10\)% contributions at \(s = 250\) GeV. The corrections are massive contributions and they must be taken into account for matching high precision data at future lepton colliders.